Analisis Risiko Likuiditas pada PT Smartfren Telecom Tbk - Nasywa Febrianti N.; Neneng Miskiyah; Divianto, Divianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the financial risk of PT Smartfren Telecom Tbk during the 2014–2023 period, focusing on both short-term and long-term liquidity aspects. The analysis employs financial ratios as measurement tools to assess the company’s financial stability and its ability to fulfill financial obligations within their respective time frames. The ratios used include the current ratio, quick ratio, interest coverage ratio, and cash flow-to-debt ratio. The results indicate that the company faces significant challenges in maintaining short-term liquidity, as reflected in the consistently low values of the current and quick ratios throughout the observation period. This condition suggests a limited ability of the company to meet its short-term obligations using available assets. In terms of long-term liquidity, although there are efforts to strengthen the capital structure, the company still encounters difficulties in meeting its long-term debt obligations. This is evident from the low interest coverage ratio and cash flow-to-debt ratio. Therefore, improving operational efficiency, implementing more effective cash management, and undertaking financial restructuring are essential measures to strengthen the company’s liquidity position sustainably.